A delayed dual risk model. Issue 1 (2nd January 2017) - Zhu, Lingjiong
ABSTRACT: In this article, we study a dual risk model with delays in the spirit of Dassios–Zhao. When a new innovation occurs, there is a delay before the innovation turns into a profit. We obtain large initial surplus asymptotics for the ruin probability and ruin time distributions. For some special cases, we get closed-form formulas. Numerical illustrations will also be provided.